Kekuatan Hukum Akta Pelepasan Hak Atas Tanah Sebagai Dasar Perolehan Hak Dari PPJB Dalam Praktik Pertanahan Di Indonesia (Lembaga Pengembangan Kinerja Dosen, 2025)
This research explores the legal status and strength of the deed of relinquishment of land rights based on the Sale and Purchase Binding Agreement (PPJB) within Indonesia’s land registration system. PPJB is a preliminary agreement that does not automatically transfer land rights, yet in practice, it is often used as a basis to create a relinquishment deed before the official Sale and Purchase Deed (AJB) is executed by a Land Deed Official (PPAT). Legal issues arise when such relinquishment deeds are not executed by a PPAT and fail to meet the formal requirements for registration, creating legal barriers in obtaining legitimate land rights. Under the Basic Agrarian Law and Government Regulation No. 24/1997, only AJB made by a PPAT can serve as a valid legal basis for rights transfer and land registration. A relinquishment deed stemming from a PPJB only has binding power in private law but cannot serve as valid proof of rights transfer against third parties. Therefore, to ensure legal certainty and rights protection, land rights transfers should be conducted through AJB and formal registration procedures. The relinquishment deed should be used only as a temporary or acknowledgment document, not as a standalone basis for land rights acquisition.